Cosmetic Compliance and the Failure of Negotiated Governance - Kimberly D. Krawiec (Washington University Law Quarterly, 2003)
Drawing on the incomplete contracts literature, this Article argues that, although the negotiated governance model provides valuable descriptive insights into the mechanisms by which legal rules develop, the model’s proponents minimize the dangers of opportunistic behavior during the renegotiation phases of governance (that is, the implementation and enforcement phases) by those with the greatest stake in the meaning of incomplete law-in this case, business organizations and legal compliance professionals, including lawyers.
Keywords: Corporate governance; Limited liability; Business ethics; Sarbanes-Oxley Act of 2002